Sapiential, liturgical and poetical texts from qumran : proceedings of the third meeting ... (Studies on the Texts of the Desert of Judah, 2000)
At the third meeting of the International Organisation for Qumran Studies, held in Oslo in 1998, a variety of papers were presented concerning the study of the Sapiential, Liturgical and Poetical Texts from Qumran. The fourteen papers selected for this volume are arranged in three sections. 'Sapiential Texts' contains four studies on different wisdom texts from Cave 4; 'Liturgical and Poetical Texts' is formed by seven papers dealing with independent poetic or liturgical compositions; while 'Qumran Wisdom and the New Testament' presents three papers that explore the relationship of wisdom materials found at Qumran and some passages of the New Testament. The volume is published in memory of Maurice Baillet, who passed away shortly before the meeting. It contains a biographical sketch and his complete bibliography provided by Emile Puech.